2008
DOI: 10.1093/ejechocard/jen221
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound imaging of periadventitial vasa vasorum in human carotid arteries

Abstract: Periadventitial contrast signal was detected in all patients and BFI thickness was higher in patient with carotid atherosclerosis and correlated with IMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 30 publications
2
49
1
1
Order By: Relevance
“…Third, our population consisted of subjects with a predominance of cardiovascular risk factors and expressed CVD (76% exhibited carotid lesions), therefore our focus was directed at assessing carotid plaque neovascularization not measurements of carotid intima-media thickness. Though, previously, Magnoni et al 12 reported on the direct association between adventitial vasa vasorum and carotid intima-media thickness. This combined approach may be valuable in future prospective studies, which includes screening of subjects considered to be at lower risk.…”
Section: Study Limitationsmentioning
confidence: 93%
“…Third, our population consisted of subjects with a predominance of cardiovascular risk factors and expressed CVD (76% exhibited carotid lesions), therefore our focus was directed at assessing carotid plaque neovascularization not measurements of carotid intima-media thickness. Though, previously, Magnoni et al 12 reported on the direct association between adventitial vasa vasorum and carotid intima-media thickness. This combined approach may be valuable in future prospective studies, which includes screening of subjects considered to be at lower risk.…”
Section: Study Limitationsmentioning
confidence: 93%
“…Adventitialderived vasa vasorum neovascularization plays a signifi cant role in atherosclerotic plaque progression and destabilization (2)(3)(4). Investigators in a recent study ( 5 ) have shown that adventitial vasa vasorum density and permeability precede an increase in intima-media thickness, endothelial dysfunction ( 6 ), and, most important, infl ammatory activity of the plaque ( 7,8 ). Plaque instability, which leads to plaque rupture and clinical events, may be triggered by the disruption and leakage of immature neovessels originating from adventitial vasa vasorum ( 9 ).…”
Section: Study Populationmentioning
confidence: 99%
“…This technique was also used for identifying and quantifying carotid artery vasa vasorum and intraplaque neovascularization in patients with atherosclerotic carotid artery lesions (10)(11)(12). A correlation was found between the inflammation observed on histopathologic analysis of the plaque after endarterectomy and the degree of intraplaque neovascularization on CEUS (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%